2(x+1)-(5+x)=-4

Simple and best practice solution for 2(x+1)-(5+x)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)-(5+x)=-4 equation:



2(x+1)-(5+x)=-4
We move all terms to the left:
2(x+1)-(5+x)-(-4)=0
We add all the numbers together, and all the variables
2(x+1)-(x+5)-(-4)=0
We add all the numbers together, and all the variables
2(x+1)-(x+5)+4=0
We multiply parentheses
2x-(x+5)+2+4=0
We get rid of parentheses
2x-x-5+2+4=0
We add all the numbers together, and all the variables
x+1=0
We move all terms containing x to the left, all other terms to the right
x=-1

See similar equations:

| C=2•3.14r | | 2x+1+x+11=27 | | |-(x-5)|=8.5 | | 7n=500 | | 3/3y+4=2/y-4 | | 7-1=-1-n | | -7/8k=-28 | | 9x-12=0.25(32x+56) | | -7/8=-28k | | 6+5(m=1)=26 | | -6+a+5a=0 | | 21=a÷3 | | -7/8k=028 | | 45=2u+9 | | 2(x^2+4x+4)-5=8 | | -6a+2a=12 | | 2n-2(4n+5)=-6(n-3) | | 1.0598x+1.01=9 | | 2(x-1)+5x=2x-(x-5) | | 1/5(25-5y)=21-3(y-4) | | 7+9(1-5c)=-34 | | 14=5v+2v | | 6+8=14+3d | | -46x=3x+7x | | -a+2a=12 | | 1+2b=5-2b | | 26=u/3-17 | | 7(x^2+4x+4)-5=8 | | 3n+2(n+5)=15 | | n+5/16=1 | | -8z=8 | | -8-3w=11 |

Equations solver categories